THE FACE OF VIOLENCE: RETHINKING THE CONCEPT OF XENOPHOBIA, IMMIGRATION LAWS AND THE RIGHTS OF NON-CITIZENS IN SOUTH AFRICA - N. Odiaka (BRICS Law Journal, 2017)
Xenophobia, simply put, is the fear or hatred of foreigners or strangers; it is embodied in discriminatory attitudes and behaviors, and often culminates in violence, abuses of all types, and exhibition of hatred. Theoretically, the best and only solution is to remove enemy images; however, it is debatable whether this can be done. In the same breath, protecting migrants’ rights may be the best way to enhance state sovereignty in a globalized world. The protection of fundamental human rights and freedoms transcends municipal and international laws. However, it is the state’s responsibility to uphold human rights through its laws and enforcement. This work examines the constitutional rights of non-citizens in South Africa within the context of its immigration law and xenophobia. The motives of xenophobia are considered. It will be argued that foreign nationals are particularly vulnerable to the restriction of their access to justice as the immigration laws and policies have not adequately guaranteed foreigners certain inalienable rights. The states uncoordinated attitude towards xenophobic attacks raises doubt as to whether there can be compliance with the sacred constitutional obligation to protect and preserve lives of all people within the country. For on the one hand the law claims to protect non-citizens while on the other, no prosecution has been made against anyone involved in xenophobic attack. The failures of the state will be observed and necessary suggestions will be proffered by this work to aid policy makers.